2015
DOI: 10.1080/03670244.2015.1041136
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Expenditure Patterns, Food Nutrient Consumption and Nutritional Vulnerability in Nigeria: Implications for Policy

Abstract: The study examined the patterns of food spending, food nutrient consumption, and nutrient deficiency profiles of households in Nigeria using a cross-sectional nationwide household survey data. Food nutrients were estimated from food expenditure data while the nutrient deficiency profiles were assessed adapting Foster et al. (1984) poverty index. The study established widespread nutritional deficiencies with low-income household cohorts bearing a greater burden of the deficiencies. Protein-protein deficiency ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…No distinction is made regarding the livelihood system or geography of the household, even though these conditions will obviously drive both production and consumption decisions as well as dietary outcomes. Analyses of household consumption point to large differences across households in relation to socioeconomic, geographic and cultural variables [30,32,33]. In particular, the regional and rural/urban dimensions of nutrition warrant a deeper analysis if it is made useful for policy-making in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No distinction is made regarding the livelihood system or geography of the household, even though these conditions will obviously drive both production and consumption decisions as well as dietary outcomes. Analyses of household consumption point to large differences across households in relation to socioeconomic, geographic and cultural variables [30,32,33]. In particular, the regional and rural/urban dimensions of nutrition warrant a deeper analysis if it is made useful for policy-making in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Brouwer et al report average daily caloric consumption from GHS for households in adult female equivalents, which is approximately 20% lower than the usual average adult equivalent. The study of Akerele (2015) computes per capita adult equivalents per rural and urban population, based on the most recent national food consumption and nutrition survey (FCNS) in 2003-04 [32]. In Aromolaran (2010), the caloric data are based on the author's survey of 480 households from semirural areas of south-western Nigeria [33].…”
Section: Extension Of Magnet For Modelling Nutrients Supply Using Thementioning
confidence: 99%
“…Cereals and grains were on average consumed daily by 81·3 % of the population. Several studies showed a contribution of cereals to the protein intake of approximately 20-40 % (36)(37)(38) . Legumes were eaten by 45·5 % of the population on average.…”
Section: Nigerian Diet and Its Contribution To Protein Intake Adequacymentioning
confidence: 99%
“…According to a study conducted in the south-east of Nigeria, animal-source products contributed only 3 % to the total daily energy intake (13) . Dairy products were found to account for barely 0·9 % of protein intake (36) . In general, dairy products were only consumed by 38·4 % of the population, with milk being consumed by only 31·9 % (Table 3).…”
Section: Nigerian Diet and Its Contribution To Protein Intake Adequacymentioning
confidence: 99%
See 1 more Smart Citation